(untitled) (Translation: The University of Toledo Journal of Medical Sciences, 2025)
Pyrethroids are a class of commonly used synthetic insecticides, widely used in agricultural and residential settings due to their efficacy and relatively low environmental impact. Nonetheless, epidemiological studies have found that exposure to pyrethroids during developmental stages is linked to risk for neurodevelopmental disorders. However, the molecular mechanisms behind these neurotoxic effects remain unclear. Our study investigates the impact of oral exposure to deltamethrin, a widely used Type II pyrethroid pesticide, on gene expression in the frontal cortex of rats. We used differential gene expression data from frontal cortex dissections from male Long-Evans rats exposed to a 3 mg/kg oral dose of deltamethrin (or vehicle) to perform a 3Pod analysis in R Studio, which included GSEA, Enrichr, and iLINCS analyses. We found that rats who were exposed to deltamethrin had significant changes in gene expression in cortex in pathways related to inflammation, apoptosis, cellular energy metabolism, and synapses. Our study provides important insight on the effects of pesticide exposure on the brain and possible treatments and preventions. This study also emphasizes the need for further research on pyrethroid pesticides and their relationship to neurodevelopmental disorders.